PENGARUH ASIMETRI INFORMASI, LEVERAGE, DAN KOMPENSASI BONUS TERHADAP MANAJEMEN LABA SHORT TERM DISCRETIONARY ACCRUAL DAN LONG TERM DISCRETIONARY ACCRUAL - LOLITA PUTRI, DEVI, PUJIONO (Jurnal Akuntansi AKUNESA, 2019)
The objective of this research is to analyze profit management by using a model of short term discretionary accrual and long term discretionary accrual of the manufacturing companies that were enlisted in BEI. The independent variables applied are information asymmetry, leverage, and bonus. The methodology used multiple linear regression analysis and purposive sampling which comprising the whole number of 162 sample in 2008-2016. The research findings indicated that between the listed variables, information asymmetry and leverage hold positive impacts on profit management of long term discretionary accrual, but did not hold any on short term discretionary accrual. Meanwhile bonus hold positive impacts on profit management of short term discretionary accrual but did not hold any on long term discretionary accrual.Keywords: Information asymmetry; leverage; bonus; short term discretionnary accrual; long term discretionnary accrual.